2020
DOI: 10.3390/ma13225116
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Austenitization Temperature and Pre-Deformation on CCT Diagrams of 23MnNiCrMo5-3 Steel

Abstract: The combined effect of deformation temperature and strain value on the continuous cooling transformation (CCT) diagram of low-alloy steel with 0.23% C, 1.17% Mn, 0.79% Ni, 0.44% Cr, and 0.22% Mo was studied. The deformation temperature (identical to the austenitization temperature) was in the range suitable for the wire rolling mill. The applied compressive deformation corresponded to the true strain values in an unusually wide range. Based on the dilatometric tests and metallographic analyses, a total of five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…After austenitizing and deformation at a temperature of 860 °C, the mean grain size was 9.7 ± 0.9 µm, but after deformation at a temperature of 1,000 °C it was roughly twice (21.7 ± 2.0 µm; the data scatter was characterized by the confidence interval with a 95% confidence level). Thus, it was confirmed that a coarser austenitic grain is associated with a slowing down of the ferritic and pearlitic transformation, the grains or formations of which are originated by a diffusion mechanism [11,12]. The reason is the formation of a smaller amount of suitable nucleation sites.…”
Section: Comparison Of Dcct Diagramsmentioning
confidence: 86%
“…After austenitizing and deformation at a temperature of 860 °C, the mean grain size was 9.7 ± 0.9 µm, but after deformation at a temperature of 1,000 °C it was roughly twice (21.7 ± 2.0 µm; the data scatter was characterized by the confidence interval with a 95% confidence level). Thus, it was confirmed that a coarser austenitic grain is associated with a slowing down of the ferritic and pearlitic transformation, the grains or formations of which are originated by a diffusion mechanism [11,12]. The reason is the formation of a smaller amount of suitable nucleation sites.…”
Section: Comparison Of Dcct Diagramsmentioning
confidence: 86%
“…The sample's average hardness value for a 100 • C/s cooling rate corresponded with the hardness of the base material. The base material's microstructure is predominantly martensitic and was the same for the 100 • C/s cooling rate, the typical cooling rate for hardening HSLA steels [36,43,45,47,48]. The first significant hardness drop was recorded at a 10 • C/s cooling rate with a 23% decrease compared with the base material.…”
Section: The Analysis Of the Hardness After Coolingmentioning
confidence: 95%
“…This process occurred with the shear transformation of austenite [44]. Hardness measurements for all samples were performed to compare with the microstructure while considering hardness the ferrite-perlite steel structure, next bainite, martensite and their mixture [4,6,36,47]. The cooling rate's effect on the values of the first and last austenite decomposition transformation temperature for both methods of determination is shown in Figure 9.…”
Section: Austenite Transformation Temperatures In Cooling Phasementioning
confidence: 99%
“…By lowering the rolling temperature, it was possible to reduce the grain size by up to 56 μm. Schindler et al [ 13 ] studied the combined effect of austenitization temperature and pre-deformation on continuous cooling transformation (CCT) diagrams of 23MnNiCrMo5-3 steel. Based on the dilatometric tests and metallographic analyses, a total of five different diagrams were constructed and compared.…”
mentioning
confidence: 99%